Checklist of the Bromeliaceae of the Serra do Cabral, Minas Gerais, Brazil, with a description of a new species - Guarçoni, Elidio A. E.; Sartori, Marcos A. (Phytotaxa, 2020)
An illustrated checklist of the species of Bromeliaceae from the Serra do Cabral, Minas Gerais state, southeastern Brazil is presented, including 20 species in 11 genera from three subfamilies. Subfamilies Tillandsioideae and Bromelioideae each contain eight species, which mainly inhabit rocky fields. Tillandsia is the most diverse genus, with six species. Subfamily Pitcairnioideae contains four species, including Dyckia spinulosa, as well as Dyckia oscari, a new species described and illustrated herein.